PENGARUH PERSEPSI MANAJEMEN ATAS KEUNGGULAN PENERAPAN E-BILLING DAN E-SPT PAJAK PERTAMBAHAN NILAI PADA KEPATUHAN PERPAJAKAN - Handayani, Milan Novita; Noviari, Naniek (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the influence of management perceptions on the advantage of e-billing and e-SPT VAT on tax compliance. Research was conducted at the Kantor Pelayanan Pajak Pratama Badung Utara. The population in this research is the Taxable Entrepreneur Firm registered in the Kantor Pelayanan Pajak Pratama Badung Utara. The number of samples in the study that as many as 87 respondents, the sampling technique through simple random sampling method. Data collection method used is survey by distributing questionnaires, respondents consisted of business owners, head of accounting and head of tax. Data analysis technique used is multiple linear regression analysis. Based on the results of analysis show that the perception of management on the advantages of e-billing and e-SPT VAT had positive effect on tax compliance.
Keywords: perception of management, the advantages of e-billing, advantages of e-SPT PPN, tax compliance